Dr. Percy Lavon Julian honored at MacMurray College - MacMurray College (1972)
Two photographs of Dr. Percy Lavon Julian (1899-1975) taken during a ceremony for the newly constructed chemistry building of MacMurray College in Jacksonville, Illinois, named in his honor. This event took place during a two-day symposium attended by more than 100 scientists and educators on May 12 and 13th, 1972. The first image depicts Dr. Julian standing beneath a plaque paying tribute to his contributions to chemistry, medicine, and humanity. The second shows Julian holding a framed picture of the Percy Lavon Julian Hall of Chemistry. Julian is internationally recognized for his pioneering research in the development of cortisone, sex hormones, soybean proteins, and firefighting foam. Over the course of his career, Julian received more than 130 chemical patents and in 1973, became the second African American, following David Blackwell (1919-2010), to be elected to the National Academy of Sciences.
Keywords: Julian, Percy Lavon, 1899-1975; Chemists; Awards; Organic compounds--Synthesis; Scientists, Black; African American chemists; Scientists